Product Packaging Innovation as a Means of Increasing Consumer Attractiveness in UMKM Kubang Jaya Village: Inovasi Pengemasan Produk sebagai Sarana Peningkatan Daya Tarik Konsumen pada UMKM Desa Kubang Jaya - Budi Maulana; Sutarti Sutarti; Anharudin Anharudin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Many efforts can be made to improve and develop MSMEs. One of them is to improve product quality and packaging. Unique, attractive and creative packaging will invite the desire to buy the product. In Kubang Jaya Village there are several MSME businesses, which are engaged in various fields, and some are engaged in food processing. To increase product sales, it is necessary to innovate, one of which is packaging innovation. This community service activity is focused on socializing the importance of packaging innovation with the aim of providing insight into the importance of various attractive and contemporary packaging to improve and develop the business going forward. Service activities include observation, planning, outreach, implementation and evaluation. After delivering the material, discussing, providing feedback and asking questions it was discovered that some participants were interested in designing their product packaging to make it more attractive. Karang Taruna youths were inspired to change the rice packaging of their wares into rice bowl packaging. Some youths even process emping products into various flavorswith attractive packaging designs